REIT implementation and conversion in South Africa - Pagiwa, Reneiloe Lehlohonolo (My University, 2017)
In 2013 new legislation was introduced allowing for the creation of a new listed property entity called a Real Estate Investment Trusts (REIT). Previously the listed property sector was dominated by two main types of property which were Property Unit Trusts (PUT) and Property Loan Stock Companies (PLS). The introduction of the REIT entity allowed existing listed property companies to convert to REIT status and for new companies to list on the Johannesburg Stock Exchange as REITs. The purpose of this study is to evaluate the impact of REIT implementation and the conversion of PLS and PUT to REIT status on shareholder wealth in South Africa. The study evaluates the change in shareholder wealth through the use of abnormal return calculations during events that led up to the implementation of REITs and conversion to REIT status. The findings show that implementation and conversion to REITs did not result in significant industry gains in shareholder wealth. The events leading to the implementation of REITs however showed positive abnormal returns out lining positive sentiments in the market. For the companies that converted to REIT status their shareholder wealth had negative performance returns. Immediate gains in shareholder wealth are not present. This indicating that the use of REITs as an investment will have to be monitored in the long term.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Building (Property Development and Management), Johannesburg, 2017
Keywords: Real estate investment trusts--South Africa; Real estate investment--South Africa; Investment analysis--South Africa; Property-South Africa